2013
DOI: 10.1371/journal.pone.0082214
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Blue Modulates Transendothelial Migration of Peripheral Blood Cells

Abstract: Vasoplegia is a severe complication after cardiac surgery. Within the last years the administration of nitric oxide synthase inhibitor methylene blue (MB) became a new therapeutic strategy. Our aim was to investigate the role of MB on transendothelial migration of circulating blood cells, the potential role of cyclic cGMP, eNOS and iNOS in this process, and the influence of MB on endothelial cell apoptosis. Human vascular endothelial cells (HuMEC-1) were treated for 30 minutes or 2 hours with different concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…An in vitro study using endothelial cells demonstrated that the immunomodulatory effect produced by MB was influenced by dose and time [19]. This finding might also be applicable to in vivo conditions and may explain the differences between the two doses of MB in our study.…”
Section: Discussionsupporting
confidence: 65%
“…An in vitro study using endothelial cells demonstrated that the immunomodulatory effect produced by MB was influenced by dose and time [19]. This finding might also be applicable to in vivo conditions and may explain the differences between the two doses of MB in our study.…”
Section: Discussionsupporting
confidence: 65%
“…For density gradient centrifugation, the fresh blood samples were underlaid with 5 ml Polymorphprep® (Axis-Shield, Oslo, Norway) and centrifuged at 450 g for 35 min. The layers of peripheral blood leukocytes (PBL), containing peripheral blood mononuclear cells (PBMC) and polymorph nuclear cells (PMNC) 37 , were aspirated and washed with PBS (Gibco, Karlsruhe, Germany). PBL were suspended in 37 °C pre-warmed RPMI 1640 (Life Technologies, Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…As previously described 37 , HuMEC-1 were partially activated with 100 μg/ml LPS (Sigma Chemical Co. St. Louis, USA) in MCDB-131 (Life Technologies, Darmstadt, Germany), whereas the other fraction of HuMEC-1 remained non-activated. The treatment of every study group was performed for 60 min under different temperature conditions ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This benefit is likely due to early attenuation of the NO induced vasodilation cascade, which reduces the severe systemic inflammatory response(15, 20). Multivariate regression confirmed early MB administration as an independent predictor of reduced risk-adjusted MAE.…”
Section: Commentmentioning
confidence: 99%